Single‐Crystalline Structure Assisted Revealing the Critical Factors for the Properties of All‐Small‐Molecule Organic Solar Cells - Chen Yang (Wiley-VCH, 2021)
All‐small‐molecule organic solar cells have attracted great interests due to their well‐defined molecular structures and suitability for investigating the relationship between the structure and properties. Herein, two small‐molecule donors (SMDs) based on DTBDT core with chlorine atoms and alkylsilyl side chains, namely, ZR‐Si3 and ZR‐Si4, are synthesized and their respective photovoltaic properties by blending them with IDIC‐4Cl and Y6 are studied. The power conversion efficiency (PCE) based on IDIC‐4Cl is higher than that of Y6 systems due to low driving force between the donors and Y6. Although the two IDIC‐4Cl systems have similar morphology, the PCE of 10.10% is attained based on ZR‐Si4, which is higher than that of ZR‐Si3‐based devices (8.12%). To obtain an in‐depth insight into the structure and performance relationship, single crystals of two SMDs and acceptors are obtained successfully. The shortest π−π stacking distance of 3.43 Å and a transport channel between the layers are observed for ZR‐Si4, which is beneficial for getting better performance.